Microplastic Bioaccumulation by Tiger Snail (Babylonia spirata): Application of Nuclear Technique Capability using Polystyrene Labelled with Radiotracer 65Zn - Andhi Susetyo; Heny Suseno; Muslim Muslim; Miftakul Munir; Anung Pujiyanto; Noor Fadzilah Binti Yusof (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Plastic waste is a solid that is difficult to decompose but can turn into environmental microplastics. Microplastics are sizes between 0.1 μm–5 mm, highly prolific anthropogenic pollutants affecting terrestrial, freshwater, and marine ecosystems. The purpose of this study was to determine the ability of Babylonia spirata to accumulate and eliminate polystyrene microplastics. This experiment uses the nuclear applications technique. The experiment consists of two methods: manufacturing microplastics and biokinetics. The manufacture of microplastics labeled Zn-65 is based on the reaction of polystyrene sulfonate with zinc to form polystyrene sulfonate Zn resin. This microplastic labeled Zn-65 is very stable in the aquatic environment, so it is used for bioaccumulation experiments. Biokinetics includes acclimatization/adaptation of the organism for seven days, bioaccumulation consists of the organism accumulating microplastics labeled Zn-65 for seven days, and depuration for seven days that were placing the organism accumulating microplastics labeled Zn-65 in water free of contamination and biokinetics calculations include the BCF (Biocontration Factor), ku (uptake constant), ke (depuration constants), and t1/2 (half-life). The experimental results show that the ability to bioaccumulate polystyrene microplastics from seawater (BCF) is 79.2 to 304.31 ml.g-1. This bioaccumulation is affected by the microplastic content in the water. The biological half-life of the microplastic is 14.54 to 41.78 d. There is a relationship between the concentration and the Ku, Ke and BCF. the polystyrene content. The experimental results show that microplastics bioaccumulate in a marine organism so that they can move through the food chain and are ultimately harmful to humans.